2015
DOI: 10.1111/vaa.12207
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous sufentanil-midazolam versus sevoflurane anaesthesia in medetomidine pre-medicated Himalayan rabbits undergoing ovariohysterectomy

Abstract: Anaesthesia with sufentanil-midazolam in medetomidine premedicated healthy rabbits is useful in the clinical and the research setting, as an alternative to sevoflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This study indicated that dexmedetomidine did not affect postoperative recovery in patients following hysterectomy, possibly related to its antisympathetic, sedative, and analgesic effects, and it also had no significant effect on normal breathing. 5 In accordance with the current results, Silva-Jr et al. 27 reported that dexmedetomidine had a better sedative effect compared with benzodiazepines, which reduced restlessness in surgical patients during the recovery period and was conducive to postoperative recovery.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study indicated that dexmedetomidine did not affect postoperative recovery in patients following hysterectomy, possibly related to its antisympathetic, sedative, and analgesic effects, and it also had no significant effect on normal breathing. 5 In accordance with the current results, Silva-Jr et al. 27 reported that dexmedetomidine had a better sedative effect compared with benzodiazepines, which reduced restlessness in surgical patients during the recovery period and was conducive to postoperative recovery.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies found that increasing anesthesia in the perioperative period may affect the quality of recovery from anesthesia, and that dexmedetomidine may improve anesthesia recovery. 5 However, although dexmedetomidine does not inhibit the respiratory system and rarely causes apnea, some studies found that it could lead to hypoxia and hypercapnia, and may have hemodynamic effects such as hypertension and hypotension. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Medetomidine is widely used in many countries for sedation in a variety of animal species and administered intramuscularly (IM) at 100–500 μg/kg in combination with other sedatives, analgesics, and/or injectable anesthetics in rabbits [ 1 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 30 ]. Kirihara et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a study from 2020 ( 21 ) it was shown that the IBP measurement system is more prone to error with higher compared to lower heart rates and that at high heart rates (120 beats per minute) the demands on the system become more stringent. Heart rates in rabbits are usually higher than 120 beats per minute, even when cardiodepressive drugs have been used for sedation or anaesthesia ( 22 ). This could have influenced the accuracy of the invasive measurement.…”
Section: Discussionmentioning
confidence: 99%